3D FSS polarizer for millimeter‐wave antenna applications. Issue 8 (1st April 2019) - Mantash, Mohamad; Denidni, Tayeb A.
Abstract: In this article, a novel wideband polarizer is presented, to convert the linear polarization of a directive antenna into circular polarization. This innovative polarizer is based on a 3D frequency selective surface (FSS) and consists of an array of 4×4 metal axial‐mode helices. The proposed broadband polarizer operates in the 28 to 31 GHz frequency band. To demonstrate the principle, the 3D FSS is applied to a linearly polarized Yagi‐Uda antenna operating in the same millimeter‐wave frequency band. The measured and simulated results, by integrating the proposed 3D polarizer in front of the antenna, show that an axial ratio smaller than 3 dB is obtained over a wide bandwidth with gain enhancement.